The Relationship between the Implementation of the PSBB Policy and the Number of Tourists in Lumajang Regency during the COVID-19 Pandemic - Al Maidah, Firdaus; Murniati, Wahyuning (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
The COVID-19 pandemic has caused several local governments to implement Large-Scale Social Restrictions (PSBB) and Community Activity Restrictions (PPKM) policies to minimize the presence of new clusters of COVID-19 spread. This policy will certainly have implications for limiting community activities, including in the tourism sector. However, there are still not many studies that examine the effect of PSBB on the tourism sector. By using two research methods, namely qualitative (descriptive analysis) and quantitative methods (correlation analysis), this study found two things that can be contributed to research on the tourism sector, especially in Lumajang Regency. First, the results found that the increase in the number of COVID-19 patients was not significantly related to the number of tourists in Lumajang Regency. Second, the results of the study also found that the implementation of the PSBB in the East Java region was significantly associated with a decrease in the number of tourists in Lumajang Regency. From these results, it can be concluded that the development of tourism in Lumajang Regency has a relationship with the implementation of the PSBB policy in the East Java region and not because of the increase in COVID-19 patients in Lumajang Regency itself.